A kind of ultrafine powder 3D printing material and preparation method thereof
By using ultra-fine powder 3D printing materials, combined with the mixing technology of belt conveyor and blower, the environmental damage, insufficient strength and high energy consumption of 3D printed building materials are solved, and efficient and environmentally friendly 3D printing materials are achieved. Suitable for high load-bearing building components and improves freeze-thaw resistance.
Patent Information
- Application Number
- CN202411406223.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Existing 3D printed building materials have problems such as destroying the natural environment, weak load-bearing strength, poor corrosion resistance and high manufacturing energy consumption.
It uses ultra-fine powder 3D printing materials, including silicon powder, magnesium oxide powder, plant fiber powder, anti-corrosion oxide powder and urea formaldehyde resin, and mixes them through the belt conveyor to prepare efficient and environmentally friendly 3D Printing materials.
It improves the compressive performance and freeze-thaw stability of 3D printing materials, reduces production energy consumption, is suitable for high-load-bearing building components, and significantly reduces the energy consumption of mixing.
Smart Images

Figure CN118908691B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing materials, and in particular to an ultrafine powder 3D printing material and a preparation method thereof. Background Art
[0002] 3D printing technology is the popular name for additive manufacturing technology. On the basis of traditional printers that can only print on a plane, it has added the ability to print another coordinate line perpendicular to the original plane direction. The working principle of 3D printing is to split a three-dimensional geometric object into several planes according to a limited and certain thickness, and use the corresponding 3D printing materials to process it layer by layer, and finally accumulate the required three-dimensional model. The processing method of additive manufacturing is more efficient and saves materials and energy. At present, 3D printing technology has been applied to the field of construction, but the existing 3D printing building materials generally have the following technical problems: Technical problems: 1. In the existing technology, the aggregate of 3D printed cement-based materials is mostly river sand, and excessive exploitation of river sand resources has caused damage to the environment; 2. The strength of 3D printed material products is limited, there is large internal stress, and it is easy to crack, and it cannot be used as a high-load-bearing component, such as a load-bearing bracket such as a photovoltaic bracket; 3. Cement-based 3D printing materials have poor corrosion resistance and are prone to carbonization reactions, resulting in large freeze-thaw changes in low temperature environments, and the structure is prone to cracking and falling off, affecting the service life of the concrete structure; 4. Traditional building materials have large mixing resistance and require a very high-power motor for stirring, which takes a long time and consumes high energy. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] The purpose of the present invention is to provide an ultrafine powder 3D printing material and a preparation method thereof, so as to solve the technical problems of the existing 3D printing building materials, such as damage to the natural environment, weak bearing strength, poor corrosion resistance and high manufacturing energy consumption.
[0005] (II) Technical solution
[0006] Content of the invention: An ultrafine powder 3D printing material, comprising the following raw materials in parts by weight: 40-60 parts of silicon micropowder, 8-12 parts of magnesium oxide powder, 8-12 parts of magnesium chloride, 5-12 parts of plant fiber powder, 0.6-1.5 parts of urea-formaldehyde resin, 6-10 parts of anticorrosive oxidation rubber powder, 0.1-0.6 parts of iron oxide colorant, and 8-12 parts of water; the plant fiber powder is composed of coconut shell fiber, jute fiber, and sisal fiber, and the mass percentage of coconut shell fiber in the plant fiber powder is not less than 50%, the anticorrosive oxidation rubber powder is composed of rice milk and shell sintered clinker, and the mass percentage of shell sintered clinker in the anticorrosive oxidation rubber powder is not less than 80%.
[0007] Preferably, the ultrafine powder 3D printing material is prepared by the following steps: Step 1: Circulating and layering silicon powder, magnesium oxide powder, plant fiber powder, anticorrosive oxide rubber powder, magnesium chloride, urea-formaldehyde resin, and iron oxide colorant on a belt conveyor so that the material layer on the conveyor belt is greater than or equal to 7 layers; Step 2: Conveying the material on the belt conveyor to a breaker for mixing, spraying and adding water to obtain the ultrafine powder 3D printing material.
[0008] Furthermore, the particle size of the silicon micropowder is greater than 800 mesh.
[0009] Preferably, the plant fiber powder is prepared by the following steps: step a, soaking the fiber raw material with 2-4wt% alkaline soaking liquid for 10-30h; step b, adding the fiber raw material prepared in step a to a steam explosion tank at a temperature of 150-200°C and a pressure of 3MPa for steam explosion treatment, and washing and drying the fiber raw material after steam explosion treatment; step c, putting the plant fiber raw material prepared in step b into a grinder and grinding it to obtain a plant fiber powder with a particle size greater than 100 mesh.
[0010] Preferably, the mass ratio of water to rice flour in the anti-corrosion oxidation gum powder is 6:1, and the shell sintered clinker is prepared by the following steps: step d. washing the shell raw material, crushing and calcining for 2 hours, and the calcination temperature is 950°C; step e. grinding the calcined shell raw material to 100 mesh to 800 mesh to obtain shell sintered clinker.
[0011] (III) Beneficial effects
[0012] The beneficial effects of the present invention are as follows: the present invention adopts silicon micropowder as aggregate, reasonably recycles and reuses solid waste, is green and environmentally friendly, adopts magnesium oxide powder and magnesium chloride as gel materials, and adopts plant fiber powder as connecting material, effectively improving the compressive performance of 3D printing materials, so that 3D printing products can be applied to high-load-bearing building components; at the same time, anti-corrosion oxidation gel powder is added to improve the freeze-thaw stability of 3D printing materials, thereby increasing the service life of 3D printing products; the preparation method of 3D printing materials and supporting equipment adopted by the present invention can significantly reduce production energy consumption, and are worthy of large-scale promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A schematic diagram of supporting equipment for preparing 3D printing materials of the present invention;
[0014] In the figure, there are a belt conveyor 1, a quantitative feeder 2, a dispersing body 3, a dispersing blade 4, a sprinkler head 5, and an auger 6. DETAILED DESCRIPTION
[0015] The invention provides an ultrafine powder 3D printing material, comprising 40 to 60 parts by weight of raw silicon micropowder, wherein the silicon micropowder is a micropowder made by crushing and grinding high-silicon tailings sand, wherein the silicon dioxide content of the silicon micropowder is greater than 90%, and the particle size exceeds 800 meshes, thereby realizing waste utilization, and the silicon micropowder is resistant to oxidation, has high hardness, can be naturally crystallized, and forms multi-chain crystalline molecules, which are used as aggregate materials to improve the strength of 3D printing materials; the material comprises 8 to 12 parts of magnesium oxide powder and 8 to 12 parts of magnesium chloride, wherein the magnesium oxide powder and magnesium chloride form a gel material similar to magnesium oxychloride cement; and 5 to 12 parts of plant fiber powder, wherein the plant fiber powder is composed of coconut shell fiber, jute fiber, and sisal fiber, wherein the coconut shell fiber has higher tensile strength, and therefore the mass percentage of the coconut shell fiber in the plant fiber powder is not less than 50%, and the plant fiber powder is used as an aggregate material and a gel material. The connecting material can significantly improve the strength of 3D printing materials; 6 to 10 parts of anti-corrosion oxide glue powder, which is composed of rice slurry and shell sintered clinker. The mass ratio of water to rice flour is 6:1. The branched starch in the rice flour acts as an inhibitor. On the one hand, it controls the growth of calcium sulfate crystals, and on the other hand, it generates a tight microstructure, which can effectively promote the adhesion between materials, thereby improving durability. The mass percentage of shell sintered clinker in the anti-corrosion oxide glue is not less than 80%, and shell sintered clinker has good anti-corrosion properties and freeze-thaw stability; 0.6 to 1.5 parts of urea-formaldehyde resin. After adding urea-formaldehyde resin, the liquid content of the slurry can be reduced, thereby reducing the shrinkage rate of the mortar, improving the stability and fluidity of the mortar, and effectively resisting the generation of cracks; 0.1 to 0.6 parts of iron oxide colorant to make the product colorful; 8 to 12 parts of water.
[0016] The present invention also provides a method for preparing ultrafine powder 3D printing materials, including the preparation of plant fiber powder:
[0017] Step a, soaking the fiber raw material with 2-4wt% alkaline soaking liquid for 10-30h;
[0018] Step b, adding the fiber raw material obtained in step a into a steam explosion tank at a temperature of 150-200° C. and a pressure of 3 MPa for steam explosion treatment, and washing and drying the fiber raw material after the steam explosion treatment;
[0019] Step c, putting the plant fiber raw material obtained in step b into a grinder and grinding it to obtain a plant fiber powder with a particle size greater than 100 mesh;
[0020] Preparation of shell sintered clinker:
[0021] Step d. Washing, crushing and calcining the shell raw material for 2 hours at a calcination temperature of 950°C;
[0022] Step e. grinding the calcined shell raw material to 100-800 mesh to obtain shell sintered clinker;
[0023] The components of the ultrafine powder 3D printing material are mixed using Figure 1 The following supporting equipment can significantly reduce the energy consumption of mixing:
[0024] Step f: Circulate and stack silicon powder, magnesium oxide powder, plant fiber powder, anticorrosive oxide rubber powder, magnesium chloride, urea-formaldehyde resin, and iron oxide colorant on a belt conveyor, so that the material layer on the conveyor belt is greater than or equal to 7 layers. Specifically, the raw materials of each component are respectively loaded into a quantitative feeder 2 for quantitative feeding, so that the powders of each component on the belt conveyor 1 are evenly layered and laid, so that the material layer on the conveyor belt is 7 layers or an integral multiple of 7 layers, so as to achieve the function of preliminary mixing;
[0025] Step g: convey the paving material on the belt conveyor to the scattering machine for mixing, spraying and adding water to obtain ultrafine powder 3D printing material. Specifically, the material on the belt conveyor 1 is input into the scattering machine body 3, and the scattering blade 4 is started during the material dropping process. The scattering blade 4 rotates at high speed to scatter and mix the falling material. After the material is scattered, it is evenly mixed with the water sprayed from the spray head 5, and finally the slurry is formed and enters the spiral auger 6 (auger 6 also has a mixing function) for transportation. The matching mixing equipment of the present invention makes full use of the potential energy of the powder falling, and completes the mixing of the materials during the paving and dropping process. Compared with the traditional high-power concrete mixing station (concrete mixing station also needs to match feeder, belt conveyor and other equipment), the power of the driving motor of the scattering blade 4 and the power of the driving motor of the auger 6 are much smaller than the power of the concrete mixing station, thereby greatly reducing the energy consumption of mixing.
[0026] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] The ultrafine powder 3D printing material of this embodiment 1 has the following components in parts by weight:
[0029] 50 parts of silicon powder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 6 parts of plant fiber powder (including 3.6 parts of coconut shell fiber, 1.2 parts of jute fiber and 1.2 parts of sisal fiber), 0.6-1.5 parts of urea-formaldehyde resin, 8 parts of anticorrosive oxidation glue powder (including 7.2 parts of shell sintered clinker and 0.8 parts of rice milk), 0.5 parts of iron oxide colorant and 10 parts of water;
[0030] The preparation method of the ultrafine powder 3D printing material described in Example 1 is as follows:
[0031] Step a, soaking the fiber raw material with 2-4wt% alkaline soaking liquid for 10-30h;
[0032] Step b, adding the fiber raw material obtained in step a into a steam explosion tank at a temperature of 150-200° C. and a pressure of 3 MPa for steam explosion treatment, and washing and drying the fiber raw material after the steam explosion treatment;
[0033] Step c, putting the plant fiber raw material obtained in step b into a grinder and grinding it to obtain a plant fiber powder with a particle size greater than 100 mesh;
[0034] Preparation of shell sintered clinker:
[0035] Step d. Washing, crushing and calcining the shell raw material for 2 hours at a calcination temperature of 950°C;
[0036] Step e. grinding the calcined shell raw material to 100-800 mesh to obtain shell sintered clinker;
[0037] The specific steps of mixing the components of ultrafine powder 3D printing materials are as follows:
[0038] Step 1: Circulate and layer silicon powder, magnesium oxide powder, plant fiber powder, anticorrosive oxide rubber powder, magnesium chloride, urea-formaldehyde resin, and iron oxide colorant on a belt conveyor, so that there are 7 layers of materials on the conveyor belt;
[0039] Step 2: The material on the belt conveyor is transported to a breaker for mixing, spraying and adding water to obtain ultrafine powder 3D printing materials.
[0040] Example 2
[0041] The ultrafine powder 3D printing material of this embodiment 2 has the following components in parts by weight:
[0042] 50 parts of silicon micropowder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 8 parts of plant fiber powder (including 4.8 parts of coconut shell fiber, 1.6 parts of jute fiber and 1.6 parts of sisal fiber), 0.6-1.5 parts of urea-formaldehyde resin, 8 parts of anticorrosive oxidation glue powder (including 7.2 parts of shell sintered clinker and 0.8 parts of rice milk), 0.5 parts of iron oxide colorant and 10 parts of water; the preparation method of the ultrafine powder 3D printing material described in Example 2 is the same as that in Example 1.
[0043] Example 3
[0044] The ultrafine powder 3D printing material of this embodiment 3 has the following components in parts by weight:
[0045] 50 parts of silicon micropowder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 10 parts of plant fiber powder (including 6 parts of coconut shell fiber, 2 parts of jute fiber, 2 parts of sisal fiber), 0.6-1.5 parts of urea-formaldehyde resin, 8 parts of anticorrosive oxidation glue powder (including 7.2 parts of shell sintered clinker and 0.8 parts of rice milk), 0.5 parts of iron oxide colorant, and 10 parts of water; the preparation method of the ultrafine powder 3D printing material described in Example 3 is the same as that in Example 1.
[0046] Example 4
[0047] The ultrafine powder 3D printing material of this embodiment 4 has the following components in parts by weight:
[0048] 50 parts of silicon powder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 8 parts of plant fiber powder (including 4.8 parts of coconut shell fiber, 1.6 parts of jute fiber, 1.6 parts of sisal fiber), 0.6-1.5 parts of urea-formaldehyde resin, 7 parts of anticorrosive oxidation glue powder (including 6.3 parts of shell sintered clinker and 0.7 parts of rice milk), 0.5 parts of iron oxide colorant, and 10 parts of water; the preparation method of the ultrafine powder 3D printing material described in Example 4 is as follows:
[0049] Step a, soaking the fiber raw material with 2-4wt% alkaline soaking liquid for 10-30h;
[0050] Step b, adding the fiber raw material obtained in step a into a steam explosion tank at a temperature of 150-200° C. and a pressure of 3 MPa for steam explosion treatment, and washing and drying the fiber raw material after the steam explosion treatment;
[0051] Step c, putting the plant fiber raw material obtained in step b into a grinder and grinding it to obtain a plant fiber powder with a particle size greater than 100 mesh;
[0052] Preparation of shell sintered clinker:
[0053] Step d. Washing, crushing and calcining the shell raw material for 2 hours at a calcination temperature of 950°C;
[0054] Step e. grinding the calcined shell raw material to 100-800 mesh to obtain shell sintered clinker;
[0055] Mixing and stirring of various components of ultrafine powder 3D printing materials:
[0056] Step f: Add silicon micropowder, magnesium oxide powder, plant fiber powder, anticorrosive oxide glue powder, magnesium chloride, urea-formaldehyde resin, iron oxide colorant and water into a concrete mixing station and stir for 4 minutes to obtain ultrafine powder 3D printing material.
[0057] Example 5
[0058] The ultrafine powder 3D printing material of this embodiment 5 has the following components in parts by weight:
[0059] 50 parts of silicon micropowder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 8 parts of plant fiber powder (including 4.8 parts of coconut shell fiber, 1.6 parts of jute fiber and 1.6 parts of sisal fiber), 0.6-1.5 parts of urea-formaldehyde resin, 9 parts of anticorrosive oxidation glue powder (including 8.1 parts of shell sintered clinker and 0.9 parts of rice milk), 0.5 parts of iron oxide colorant and 10 parts of water; the preparation method of the ultrafine powder 3D printing material described in Example 5 is the same as that in Example 4.
[0060] Comparative Example 1
[0061] The 3D printing material of this comparative example 1, according to the weight parts, its components are as follows: 50 parts of silicon micropowder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 0.6-1.5 parts of urea-formaldehyde resin, 8 parts of anticorrosive oxidation glue powder (including 7.2 parts of shell sintered clinker and 0.8 parts of rice milk), 0.5 parts of iron oxide colorant, and 10 parts of water;
[0062] The preparation method of the 3D printing material described in Comparative Example 1 is as follows:
[0063] Preparation of shell sintered clinker:
[0064] Step a. Wash, crush and calcine the shell raw material for 2 hours at a calcination temperature of 950°C;
[0065] Step b. grinding the calcined shell raw material to 100 mesh to 800 mesh to obtain shell sintered clinker;
[0066] The specific steps for mixing the components of ultrafine powder 3D printing materials are as follows:
[0067] Step c: Circulating and layering silicon micropowder, magnesium oxide powder, anticorrosive oxide rubber powder, magnesium chloride, urea-formaldehyde resin, and iron oxide colorant on a belt conveyor, so that there are 6 layers of material on the conveyor belt;
[0068] Step d: convey the paving material on the belt conveyor to a scattering machine for mixing, spraying and adding water to obtain 3D printing materials.
[0069] Comparative Example 2
[0070] The 3D printing material of this comparative example 2, in terms of weight parts, has the following components: 50 parts of silicon micropowder, 10 parts of magnesium oxide powder, 10 parts of magnesium chloride, 8 parts of plant fiber powder (including 4.8 parts of coconut shell fiber, 1.6 parts of jute fiber, and 1.6 parts of sisal fiber), 0.6-1.5 parts of urea-formaldehyde resin, 0.5 parts of iron oxide colorant, and 10 parts of water; the preparation method of the 3D printing material described in comparative example 2 is as follows:
[0071] Step a, soaking the fiber raw material with 2-4wt% alkaline soaking liquid for 10-30h;
[0072] Step b, adding the fiber raw material obtained in step a into a steam explosion tank at a temperature of 150-200° C. and a pressure of 3 MPa for steam explosion treatment, and washing and drying the fiber raw material after the steam explosion treatment;
[0073] Step c, putting the plant fiber raw material obtained in step b into a grinder and grinding it to obtain a plant fiber powder with a particle size greater than 100 mesh;
[0074] Step e: Add silicon micropowder, magnesium oxide powder, plant fiber powder, magnesium chloride, urea-formaldehyde resin, iron oxide colorant and water into a concrete mixing station and stir for 4 minutes to obtain 3D printing materials.
[0075] Table 1 records the compressive strength, freeze-thaw test stability, and power consumption per cubic meter of mixed 3D printing materials of the embodiments and comparative examples:
[0076]
[0077] It should be noted that the compressive strength performance test of the embodiments of the present invention and the comparative examples was carried out on the prepared specimens according to the specification GB / T17671-1999. The size of the tested component was 40 mm×40 mm×160 mm. The mechanical strength was tested at two ages of 7 days and 28 days respectively. At least 3 specimens were tested in each group to calculate the average strength value. The freeze-thaw test of the present invention was carried out in accordance with the "quick freezing method" in (GBJ82-85)
[255] : the freezing temperature of the specimen was -17±2°C, the melting temperature was 8±2°C, and a single freeze-thaw cycle should be completed within 2 to 4 hours. The concrete mixing station of the embodiments of the present invention and the comparative examples adopted the HZS120 model, the main mixer power was 77KW, and the driving motor of the scattering blade 4 adopted a 20KW power to meet the mixing requirements.
[0078] It can be seen from the data recorded in Table 1 that, from Implementation 1 to Example 3, as the amount of plant fiber powder added increases (other components are the same), the compressive strength gradually increases, and significantly exceeds the compressive strength of ordinary C30 concrete. However, in Example 3, it is known that when the amount of plant fiber powder added is too much, the mass loss rate of the freeze-thaw test specimen increases. It can be seen that when the mass fraction of plant fiber powder is 8, the comprehensive performance of the specimen is optimal. When no plant fiber powder is added in Comparative Example 1, the compressive strength is greatly reduced. It can be seen that the addition of plant fiber powder can significantly improve the compressive strength of the specimen.
[0079] It can be seen from the data recorded in Table 1 that with the increase in the amount of anti-corrosion oxide glue powder added in Implementation 4, Example 2, and Example 5, the mass loss rate of the freeze-thaw test specimens is reduced. However, it is known in Example 5 that when the amount of anti-corrosion oxide glue powder added is large, the compressive strength of the specimen decreases. It can be seen that the comprehensive performance of the specimen is optimal when the mass fraction of the anti-corrosion oxide glue powder is 8. When the anti-corrosion oxide glue powder is not added in Comparative Example 2, the mass loss rate of the freeze-thaw test specimen is significantly increased. It can be seen that the addition of anti-corrosion oxide glue powder can significantly improve the freeze-thaw resistance of the specimen. In summary, Example 2 can be used as a preferred embodiment; from Example 1 to Example 3 and Comparative Example 1 in Table 1, it can be concluded that the energy consumption of the preparation method of the ultrafine powder 3D printing material used in the present invention is significantly reduced. Compared with the traditional concrete mixing station, the supporting equipment used in the preparation method of the present invention can save energy by about 60%.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A superfine powder 3D printing material, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of silicon micropowder, 8-12 parts of magnesium oxide powder, 8-12 parts of magnesium chloride, 5-12 parts of plant fiber powder, 0.6-1.5 parts of urea-formaldehyde resin, 6-10 parts of anticorrosive oxidation rubber powder, 0.1-0.6 parts of iron oxide colorant and 8-12 parts of water; the plant fiber powder is composed of coconut shell fiber, jute fiber and sisal fiber, the mass percentage of coconut shell fiber in the plant fiber powder is not less than 50%, the anticorrosive oxidation rubber powder is composed of rice milk and shell sintered clinker, the mass percentage of shell sintered clinker in the anticorrosive oxidation rubber powder is not less than 80%.
2. The ultrafine powder 3D printing material according to claim 1, characterized in that: The ultrafine powder 3D printing material is prepared by the following steps: Step 1: Circulate and layer silicon powder, magnesium oxide powder, plant fiber powder, anticorrosive oxide rubber powder, magnesium chloride, urea-formaldehyde resin, and iron oxide colorant on a belt conveyor, so that the material layer on the conveyor belt is greater than or equal to 7 layers; Step 2: The material on the belt conveyor is transported to a breaker for mixing, spraying and adding water to obtain ultrafine powder 3D printing materials.
3. The ultrafine powder 3D printing material according to claim 1, characterized in that: The particle size of the silicon micropowder is greater than 800 meshes.
4. The ultrafine powder 3D printing material according to claim 1, characterized in that: The plant fiber powder is prepared by the following steps: Step a, soaking the fiber raw material with 2-4wt% alkaline soaking liquid for 10-30h; Step b, adding the fiber raw material obtained in step a into a steam explosion tank at a temperature of 150-200° C. and a pressure of 3 MPa for steam explosion treatment, and washing and drying the fiber raw material after the steam explosion treatment; Step c, putting the plant fiber raw material obtained in step b into a grinder and grinding it to obtain plant fiber powder with a particle size greater than 100 meshes.
5. The ultrafine powder 3D printing material according to claim 1, characterized in that: The mass ratio of water to rice flour in the anti-corrosion oxidation glue powder is 6:1, and the shell sintered clinker is prepared by the following steps: Step d. Washing, crushing and calcining the shell raw material for 2 hours at a calcination temperature of 950°C; Step e. Grind the calcined shell raw material to 100-800 mesh to obtain shell sintered clinker.
